Dose-dependent Effects of PRC2 and HDAC Inhibitors on Cardiomyocyte Hypertrophy Induced by Phenylephrine - Zhao, Zhenyi; Lv, Jian; Guo, Ningning; Guo, Qiuxiao; Zeng, Sai; Fang, Yu; Chen, Weixin; Wang, Zhihua (Current Drug Targets, 2023)
Introduction: Postnatal cardiomyocytes respond to stress signals by hypertrophic growth and fetal gene reprogramming, which involves epigenetic remodeling mediated by histone methyltransferase polycomb repressive complex 2 (PRC2) and histone deacetylases (HDACs). However, it remains unclear to what extent these histone modifiers contribute to the development of cardiomyocyte hypertrophy. Methods: Neonatal rat ventricular myocytes (NRVMs) were stimulated by phenylephrine (PE; 50μM) to induce hypertrophy in the presence or absence of the PRC2 inhibitor GSK126 or the HDACs inhibitor Trichostatin A (TSA). Histone methylation and acetylation were measured by Western blot. Cell size was determined by wheat germ agglutinin (WGA) staining. Cardiac hypertrophy markers were quantified by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Results: PE treatment induced the expression of cardiac hypertrophy markers, including natriuretic peptide A (Nppa), natriuretic peptide B (Nppb), and myosin heavy chain 7 (Myh7), in a time-dependent manner in NRVMs. Histone modifications, including H3K27me3, H3K9ac, and H3K27ac, were dynamically altered after PE treatment. Treatment with TSA and GSK126 dose-dependently repressed histone acetylation and methylation, respectively. While TSA reversed the PE-induced cell size enlargement in a wide range of concentrations, cardiomyocyte hypertrophy was only inhibited by GSK126 at a higher dose (1μM). Consistently, TSA dose-dependently suppressed the induction of Nppa, Nppb, and Myh7/Myh6 ratio, while these indexes were only inhibited by GSK126 at 1μM. However, TSA, but not GSK126, caused pro-hypertrophic expression of pathological genes at the basal level. Conclusion: Our data demonstrate diversified effects of TSA and GSK126 on PE-induced cardiomyocyte hypertrophy, and shed light on epigenetic reprogramming in the pathogenesis of cardiac hypertrophy.
Keywords: epigenetic reprogramming